The diagenetic history of Oligocene-Miocene sandstones of the Austrian north Alpine foreland basin. (November 2016) - Grundtner, M.-L.; Gross, D.; Linzer, H.G.; Neuhuber, S.; Sachsenhofer, R.F.; Scheucher, L.
Abstract: Diagenesis is an essential tool to reconstruct the development of reservoir rocks. Diagenetic processes - precipitation and dissolution - have an influence on pore space. The present paper aims to study the diagenetic history of deep-marine sandstones of the Austrian Alpine Foreland Basin. To reach that goal, sediment petrology and diagenetic features of more than 110 sandstone samples from water- and gas-bearing sections from gas fields within the Oligocene-Miocene Puchkirchen Group and Hall Formation has been investigated. Special emphasis was put on samples in the vicinity of the gas-water contact (GWC). The sediment petrography of sandstones of Puchkirchen Group and Hall Formation is similar; hence their diagenesis proceeded the same way. In fact, primary mineralogy was controlled by paleo-geography with increasing transport distance and diverse detrital input. Sediment petrographically, investigated sandstones from the water-bearing horizon seemed quite comparable to the gas-bearing sediments. In general, they can be classified as feldspatic litharenites to litharenites and display porosities of up to 30% and permeabilities of up to 1300 mD. The carbon and oxygen isotopic composition of bulk carbonate cements from these sandstones range from−3.8 to +2.2 and from −7.5 to +0.2‰ [VPDB]. However, near the Gas-Water Contact (GWC) a horizon with low porosities (<3%) and permeabilities (<0.1 mD) is present. This zone is completely cemented with calcite, which has a blocky/homogenous morphology. A slight, but significant negative shift in δ18O isotopy (−2.5‰) is evident. During early diagenesis the first carbonate generations formed. First a fibrous calcite and afterwards a micritic calcite precipitated. Further siliciclastic minerals, such as quartz and feldspar (K-feldspar and minor plagioclase), exhibit corroded grains. Occasionally, clay minerals (illite; smectite, chlorite) formed as rims around detrital grains. Late diagenesis is indicated by the formation of a low permeable zone at the GWC. Highlights: Diagenesis of Puchkirchen Group and Hall Formation proceeded the same way. Water-bearing sandstones are diagenetically comparable to gas-bearing zones. Early diagenetic carbonate cementation impeded further compaction. Corrosion of early carbonate account for higher porosity and permeability. A low permeable zone between the water- and gas-bearing horizons developed.